The genetics of occupational asthma development among workers exposed to diisocyanates: A systematic literature review with meta-analysis - Word, Laura J.; McAden, Emily P.; Poole, Charles; Nylander-French, Leena A. (Frontiers in Genetics, 2022)
Diisocyanates are widely used compounds that pose a safety concern for workers in occupations within the spray-paint, spray-foam insulation, and furniture varnish industries. Epidemiological studies show that only a subset of workers exposed to diisocyanates develop diisocyanate-induced occupational asthma (diisocyanate asthma, DA), indicating that genetic susceptibility may play a role. The purpose of this systematic literature review was to compile and meta-analyze the reported data on genetic susceptibility markers for DA. Three databases (Embase, Pubmed, and Scopus) were searched and 169 non-duplicate publications were identified, of which 22 relevant occupational studies were included in this review. Researchers reported prevalence odds ratios (PORs) for 943 comparisons in 82 different genes/serotypes. Protein network functions for the DA-associated genes from this review include: antigen processing, lymphocyte activation, cytokine production regulation, and response to oxidative stress. Meta-analysis of comparisons between workers with DA and controls was conducted for 23 genetic markers within: CTNNA3, GSTM1, GSTP1, GSTT1, HLA-C, HLA-DQB1, HLA-DR1, HLA-DR3, HLA-DR4, HLA-DR7, and HLA-DR8. These genes code for proteins that are involved in cell-cell adhesions (CTNNA3), glutathione conjugation for xenobiotic metabolism (GST gene family), and immune system response (HLA gene family). The most compelling pooled PORs were for two studies on CTNNA3 (increased DA risk: rs10762058 GG, rs7088181 GG, rs4378283 TT; PORs 4.38-4.97) and three studies on HLA-DR1 (decreased DA risk, POR 0.24). Bioinformatics of the predicted protein pathways for DA shows overlap with biomarker-associated pathways in workers before development of asthma, suggesting overlap in toxicokinetic and toxicodynamic pathways of diisocyanates. The control groups were also compared against each other and differences were negligible. Suggestions for improving future research are also presented. Of the highest importance, the literature was found to be profoundly publication-biased, in which researchers need to report the data for all studied markers regardless of the statistical significance level. We demonstrate the utility of evaluating the overlap in predicted protein pathway functions for identifying more consistency across the reported literature including for asthma research, biomarker research, and in vitro studies. This will serve as an important resource for researchers to use when generating new hypothesis-driven research about diisocyanate toxicology.